Žanrska identiteta in medbesedilnost - Juvan, Marko (Primerjalna književnost, 2002)
In genology anti-essentialism has led to the thesis that genres are merely systems of differences indefinable in terms of the form or content which can be displayed in texts. The concept of intertextuality can now help explain genre identity differently: genres live off social practices, which frame intertextual and meta-textual links and references to prototypical text, textual series
Keywords: literarna teorija; literary theory; literarne zvrsti; literarne vrste; literarni žanri; genologija; tekstna lingvistika